A South Asian Identity Constructed By The Indo-Pacific Discourse: India - Yildiz, Merve (Cappadocia Journal of Area Studies, 2023)
It has been estimated that by 2050, four of the top five economies in the world will all be in Asia, with India, Japan and Indonesia all taking a spot alongside China in surpassing the United States, and revealing a global shift toward the Asian axis. While the Asia-Pacific discourse that has emerged since the Cold War promotes a China-centered understanding of Asia, a South Asian country, India, is emerging as a second rising power on the Asian continent and is taking a central position in the region. The continuing discourse will play an active role in the construction of a South Asian identity and its acceptance in the international arena. The present study first focuses on critical geopolitics. Then, through an analysis of the formal and practical geopolitical discourse in India, as an accepted research approach in critical geopolitics, an attempt will be made to reveal the ongoing construction of a South Asian identity. This study addresses the countries in the region as a whole, examining the South Asian identity that is being constructed with India at the center, and including also India’s formal and practical discourses. The study aims to reveal how India is trying to construct a South Asian identity through the Indo-Pacific discourse.